A spectroscopic study of IRAS F10214+4724 - Serjeant, S; Rawlings, S; Lacy, M; McMahon, R; Lawrence, A; Rowan-Robinson, M; Mountain, M (1998)
The z=2.286 IRAS galaxy F10214+4724 remains one of the most luminous galaxies in the Universe, despite its gravitational lens magnification. We present optical and near-infrared spectra of F10214+4724, with clear evidence for three distinct components: lines of width ~1000 km/s from a Seyfert-II nucleus; <~200 km/s lines which are likely to be associated with star formation; and a broad ~4000 km/s CIII] 1909ang emission line which is blue-shifted by ~1000 km/s with respect to the Seyfert-II lines. Our study of the Seyfert-II component leads to several new results, including: (i) From the double-peaked structure in the Ly alpha line, and the lack of Ly beta, we argue that the Ly alpha photons have emerged through a neutral column of N_H ~ 2.5 x 10^{25}/m^2, possibly located within the AGN narrow-line region as argued in several high redshift radiogalaxies. (ii) The resonant O VI 1032,1036ang doublet (previously identified as Ly beta) is in an optically thick (1:1) ratio. At face value this implies an an extreme density (n_e ~ 10^{17}/m^3) more typical of broad line region clouds. However, we attribute this instead to the damping wings of Ly beta from the resonant absorption. (iii) A tentative detection of HeII 1086 suggests little extinction in the rest-frame ultraviolet.